Pengajaran Bahasa Inggris Bagi Mahasiswa Berkebutuhan Khusus Di Kelas Inklusif: Analisis Kebijakan, Tantangan Dan Strategi Di Perguruan Tinggi - Tefa, Antonia; Ati, Serafina Natalia Ili (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2025)
Teaching English to students with Special Educational Needs (SEN) in inclusive classrooms is a challenge for lecturers as they must take into account a variety of factors, including the type of disability students have, students’ English proficiency level, and effective learning strategies. Educational institutions may not provide adequate resources to support the teaching process, including adapted textbooks, learning software, or other instructional aids. Although there are several books and articles that focus on teaching English to students with SEN, most of the resources are not available to teachers who do not have institutional access to academic literature or funds to purchase them. Therefore, there is a need for adequate literature and preparation programs that provide lecturers with practices and strategies to teach English to SEN students. This qualitative study aims to analyze the practice of teaching English in inclusive classrooms at the university level by exploring the policies and challenges faced by lecturers who teach students with SEN. In addition, this study also aims to explore the approaches or strategies used to overcome the challenges that arise. Data were collected through interviews, observations, and documentation. The results of the study indicate that although inclusive policies have been generally adopted, their implementation still faces various obstacles, such as limited resources, lack of lecturer training, and minimal adaptation of the curriculum and teaching materials. On the other hand, various strategies have been developed, including differentiated learning approaches, the use of adaptive media, and active involvement of lecturers in designing learning strategies that suit students' needs. This study concludes that effective and inclusive English teaching requires synergy between institutional policies, lecturers’ readiness, and ongoing support systems.